PERAN LEMAK COKLAT DALAM MEKANISME PRODUKSI PANAS - Siti Arifah; Kartinah Kartinah (Jurnal Berita Ilmu Keperawatan, 2008)
Thermoregulation system have two process heat production, they are shivering and non shivering thermogenesis. Non shivering thermogenesis more happens in newborn human especially to adapt of low temperatures. The prime role of this non shivering thermogenesis is Brown Adipose Tissue (brown fat). Brown fat contain many mitochondria that are able to use the fatty acids released by lipolysis for thermogenesis. Brown fat helping to raise body temperature. Brown fat serves to dispose of excess energy so that not all calories consumed will be stored.